Aminomethyl‐Functionalized Carbon Nanotubes as a Host of Small Sulfur Clusters for High‐Performance Lithium–Sulfur Batteries. Issue 10 (1st April 2020) - Li, Fen; Tao, Jiayou; Zou, Zhijun; Li, Chang; Hou, Zhaohui; Zhao, Jijun
Abstract: Here we propose an effective strategy to stabilize small sulfur species by using aminomethyl‐functionalized carbon nanotubes (AM‐CNT) without impairing the conductive channel of the carbon nanotube (CNT) cathode. The linear S n clusters can be anchored strongly to the AM‐CNT for the favorable size of n= 5 and the maximum size of n= 6 in the production of the cathode, which depresses the mass loss of active sulfur effectively and eliminates the formation of high‐order polysulfides completely during the discharge process. The most stable 3 D cross‐linked Inter‐S5 ‐AM‐CNT network shows a fast electron transfer redox reaction through the CNT skeleton that possesses a theoretical capacity of 1337 mA h g −1 (based on sulfur) or 592 mA h g −1 (based on the cathode). The discharge products of the linear S5 cluster tend to form a hyperbranched tight structure through N⋅⋅⋅S⋅⋅⋅Li bridges that are fully impregnated in the AM‐CNT bundles, and thus stabilize the entire system. Importantly, this study provides vital guidance into how to design cathodes based on small sulfur clusters for Li‐S batteries to depress the shuttle effect intrinsically during charge–discharge cycles, which can be extended to the other small‐sulfur‐cluster‐based batteries. Abstract : Shoulda put a sulfur on it : The delicate hyperbranched composite of small sulfur clusters on aminomethyl‐functionalized carbon nanotubes (S5 ‐AM‐CNT) exhibits excellent structural stability and eliminates the formation of high‐order polysulfide intermediates. Interestingly, the discharge products tend to form a cross‐linked tight cluster structure through N⋅⋅⋅S⋅⋅⋅Li bridges that is fully impregnated in the AM‐CNT bundles, and thus stabilizes the whole system.